Blood Borne Viral Infections in Transplantation: Hepatitis Viruses and Retroviruses - RP Bryce Larke (Canadian Journal of Infectious Diseases)
Hepatitis viruses B (HBV), C (HCV) and D (HDV) and the retroviruses human immunodeficiency virus (HIV-1) and human T celllymphotropic virus type I (HTLV-1) and type ll (HTLV-11) have been transmitted from infected organ and tissue donors to allograft recipients. Ascertainment of personal risk factors by health questionnaire may exclude volunteer blood donors recently exposed to transmissible diseases who could be in the 'window period' of the infection, when routine serological screening tests are negative. Difficulty in obtaining historical evidence of possible recent exposure from a critically ill prospective organ donor may make the residual risk of infection slightly higher than the risk estimated per unit of transfused products from serologically screened volunteer blood donors. Current estimates of residual risk from transfusion based on United States data are: one in 200,000 units for HBV; one in 2000 to one in 6000 units for HCV; one in 40.000 lo one in 60,000 units for HIV-1; and one in 69,272 units for HTLV-1/11. Despite recent improvements in anti-HCV testing, current screening assays underestimate the incidence of transmission and prevalence of HCV infection among immunosuppressed organ recipients: evidence of ongoing HCV infection depends on detection of HCV RNA by polymerase chain reaction. Determination of I-IIV-1 p24 antigen may facilitate identification of prospective organ donors in ll1e window period of early infection and may enhance serological follow-up of allograft recipients al risk of transplantation-associated HIV-1 infection. Highly sensitive assays that can be completed very rapidly are needed to ensure greater safely for the recipient of an emergency organ transplant, where time to screen a prospective donor for infectious diseases may be extremely limited.